Design and Craft Education in Iceland, Pedagogical Background and Development: A literature review - Ólafsson, Brynjar; Thorsteinsson, Gisli (The Design and Technology Association, 2009)
Sloyd pedagogy was introduced towards the close of the18th century to Icelandic educators. Subsequently craft was established as a specific subject aimed at general education. In the beginning craft was called “school industry,” to distinguish it from “home industry” whose aim was to help homes to be self-sufficient for commercial purposes. Different curricula focusing mainly on craft were developed until 1999 when craft was re-established as a new technological subject, based on a rationale for technological literacy, innovation and design. The new subject, Design and Craft was influenced by the national curricula of New Zealand, Canada and England and a specific Icelandic model for Innovation Education. Design and Craft education is compulsory for all grades 1-8 (ages 6-13), but optional for grades 9-10 (ages14-15). In the new subject students base their idea generation and design on authentic problems and make their artefacts from resistant materials. They design systems based on electronic circuits, mechanisms, pneumatics and structures. In this article the authors describe the pedagogical background of the subject and the curriculum development.